Laser applications in medical diagnostics - Horova, V. O. (ХНУРЕ, 2025)
This work is devoted to the usage of modern laser technologies in medicine. The most informative laser diagnostic methods include optical coherence tomography, Raman spectroscopy, and laser Doppler flowmetry, which provide high-resolution imaging and detailed analysis of biological tissues. The high accuracy, maximum safety and minimal invasiveness of laser technologies provide them with a significant role in medical diagnostics, not only improving diagnostics, but also facilitating early detection of diseases, which significantly increases the chances of successful treatment and improves the patients' quality of life.
Keywords: laser; optical coherence tomography